Penerapan Aplikasi Question AI (Artificial Intelligence) untuk Meningkatkan Hasil Belajar Peserta Didik Paket C di UPT Sanggar Kegiatan Belajar Mojokerto - Yusvano, Denta Gara; Susilo, Heryanto (J+PLUS UNESA, 2024)
This research aims to describe and analyze the application of the Question AI (Artificial Intelligence) application to improve the learning outcomes of Package C students at UPT Mojokerto Learning Activities Studio. The research method used is a descriptive qualitative research method. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results obtained from implementing the Question AI (Artificial Intelligence) application to improve the learning outcomes of Package C students at UPT Mojokerto Learning Activity Studio are increasing the effectiveness and efficiency of the learning process for Package C students as well as increasing student learning outcomes by implementing the Question AI (Artificial Intelligence) application. Intelligence as a learning medium. This can happen because of good collaboration and coordination between learning instructors and students, mutual involvement in the teaching and learning process and awareness to improve the quality of learning by using the Question AI application media. In this way, the process of improving student learning outcomes in cognitive, affective and psychomotor aspects can be faster and more accurate.